(E)-3-(3,4-Dimethoxyphenyl)-1-(2-hydroxyphenyl)prop-2-en-1-one - Jasinski, Jerry P. (International Union of Crystallography, 2011)
In the title compound, C(17)H(16)O(4), the dihedral angle between the mean planes of the hydroxyphenyl and dimethoxyphenyl rings is 5.9 (6)°. The mean plane of the prop-2-en-1-one group makes dihedral angles of 3.6 (0) and 2.6 (7)° with the hydroxyphenyl and dimethoxyphenyl rings, respectively. An intramolecular O—H⋯O hydrogen bond occurs. The crystal packing is stabilized by weak intermolecular C—H⋯O contacts and π–π stacking interactions [centroid–centroid distance = 3.6571 (8) Å].